Dampak Pariwisata terhadap Kualitas Air Danau Beratan Berdasarkan Parameter BOD dan COD - Agustina, Arik; Muliadiasa, I Ketut (Jurnal Studi Perhotelan dan Pariwisata, 2022)
Purpose: The aims of this research is to analyze the effect of tourism on the water quality of Lake Beratan using BOD and COD parameters. Methodology: His research method uses descriptive quantitative through environmental analysis. Lake Beratan water sampling was carried out at 3 points, namely point 1 representing habitation and agriculture, point 2 representing the middle part of the lake, and point 3 representing the tourist area. The information obtained was compared with the Class 1 Seawater Quality Standards Government Regulation Number 22 of 2021. Results: The results showed that the BOD parameters still met the quality standards, so there was not too much organic contamination in Lake Beratan. While the COD parameter exceeds the quality standard, namely Point 1, which is 16 mg/L; point 2 is 12 mg/L and point 3 is 12 mg/L caused by domestic waste around Lake Beratan such as household activities, agriculture, restaurants and tourism. Seeing the high domestic polluters, it is hoped that the government will pay attention to policies in environmental management and work together with local communities, tourists and visitors in protecting the environment. Limitations: The limitation of this study lies in the lack of other supporting parameters used as indicators of water pollution such as phosphate, E.coli and Total coli, it is necessary to test these parameters to determine the water conditions of Lake Beratan more thoroughly. Contribution: The output from this study are expected to be one of the references in making policies based on the data presented to make the right policies, especially to increase the positive of Lake Beratan.